Sorption properties of magnesium-potassium phosphate matrix - Dikiy, N.P.; Dovbnya, A.N.; Lyashko, Yu.V.; Medvedev, D.V.; Medvedeva, E.P.; Saenko, S.Y.; Shkuropatenko, V.A.; Tarasov, R.V.; Fedorets, I.D. (Вопросы атомной науки и техники, 2015)
Sorption characteristics of fine-dispersed magnesium-potassium phosphate ceramics KMgPO₄·6H₂O for immobilization of ¹³⁷Cs was investigated. The Cs specific capacity 2.97 mg/g at pH=4 was detected. The high selectivity of the ion exchange of KMgPO₄·6H₂O out of dilute solutions was caused by various values of hydration radii of potassium and cesium. There is change in solution pH in dynamics studies toward higher values, apparently due to leaching of movable potassium out of ceramics. The high chemical and radiation resistance of ceramic are confirmed.